Respuesta :
Hey there! I'm happy to help!
Here is our equation
3x - 4 (2x - 5) = 15
First, we will sue the distributive property to remove the parentheses. The term outside the parentheses is -4, so that is what we multiply the insides by.
3x-8x+20=15
We combine our like terms (our x-values).
-5x+20=15
We subtract 20 from both sides.
-5x=-5
We divide both sides by -5.
x=1
Have a wonderful day and keep on learning! :D
Answer: x = 1
Step-by-step explanation:
Given
3x - 4 (2x - 5) = 15
Expand parentheses and apply the distributive property
3x - 4 · 2x - 4 · (-5) = 15
3x - 8x + 20 = 15
Combine like terms
(3x - 8x) + 20 = 15
-5x + 20 = 15
Subtract 20 on both sides
-5x + 20 - 20 = 15 - 20
-5x = -5
Divide -5 on both sides
-5x / -5 = -5 / -5
[tex]\boxed{x=1}[/tex]
Hope this helps!! :)
Please let me know if you have any questions